The anthropometric and physical qualities of women`s rugby league Super League and international players; identifying differences in playing position and level - Scantlebury, S.; McCormack, S.; Sawczuk, T.; Emmonds, S.; Collins, N.; Beech, J.; Ramirez, C.; Owen, C.; Jones, B. (PLOS ONE, 2022)
Participation in women`s rugby league has been growing since the foundation of the English women`s rugby league Super League in 2017. However, the evidence base to inform women`s rugby league remains sparse. This study provides the largest quantification of anthropometric and physical qualities of women`s rugby league players to date, identifying differences between positions (forwards & backs) and playing level (Women`s Super League [WSL] vs. International). The height, weight, body composition, lower body strength, jump height, speed and aerobic capacity of 207 players were quantified during the pre-season period. Linear mixed models and effects sizes were used to determine differences between positions and levels. Forwards were significantly (p < 0.05) heavier (forwards: 82.5 ± 14.8kg; backs: 67.7 ± 9.2kg) and have a greater body fat % (forwards: 37.7 ± 6.9%; backs: 30.4 ± 6.3%) than backs. Backs had significantly greater lower body power measured via jump height (forwards: 23.5 ± 4.4cm; backs: 27.6 ± 4.9cm), speed over 10m (forwards: 2.12 ± 0.14s; backs: 1.98 ± 0.11s), 20m (forwards: 3.71 ± 0.27s; backs: 3.46 ± 0.20s), 30m (forwards: 5.29 ± 0.41s; backs: 4.90 ± 0.33s), 40m (forwards: 6.91 ± 0.61s; backs: 6.33 ± 0.46s) and aerobic capacity (forwards: 453.4 ± 258.8m; backs: 665.0 ± 298.2m) than forwards. Additionally, international players were found to have greater anthropometric and physical qualities in comparison to their WSL counterparts. This study adds to the limited evidence base surrounding the anthropometric and physical qualities of elite women`s rugby league players. Comparative values for anthropometric and physical qualities are provided which practitioners may use to evaluate the strengths and weaknesses of players, informing training programs to prepare players for the demands of women`s rugby league.